Geothermics Heat Flow in the Lithosphere - Pasquale, Vincenzo; Verdoya, Massimo; Chiozzi, Paolo (SpringerBriefs in Earth Sciences, 2014)
After a brief review of global tectonics and the structure of the crust and upper mantle, the basic relations of conductive heat transport and the rock thermal properties are introduced as well as the various methods for measuring thermal conductivity and heat generation due to the decay of radioactive elements. The authors analyze geothermal flow and the thermal state of the lithosphere and deep interior and discuss the fundamental problems related to the formation, upwelling mechanisms, solidification and cooling of magmas. The text presents analytical methods that allow us to gain information on heat and groundwater flow from the analyses of temperature-depth data. It also provides ample data and examples to facilitate understanding of the different topics. This book is useful to researchers and graduate students interested in pure and applied geothermics.